Implementation of Blockchain in Minimizing Tax Avoidance of Cryptocurrency Transaction in Indonesia - Siti Kurnia Rahayu (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this research is to determine the potential risk of tax losses caused by cryptocurrencies, to identify miners and cryptocurrency users, and to formulate a tax avoidance countermeasure strategy related to cryptocurrency transactions. This study uses qualitative research methods with literature study techniques. The type of data used in the form of textual includes definitions, concepts and arguments contained in the literature relevant to the research problem. The data used are primary data sourced from research articles from journals, and secondary data sourced from supporting documents. The data reduction and data analysis process include data display and content analysis. The results of this research show that the implementation of blockchain technology in the Indonesian tax system is a database integration model that can solve the problems of the underground economy in cryptocurrency transactions. The reason for the results of this study is that regulation of cryptocurrency transactions into the realm of regulation can be done through vertical regulation of the blockchain market, with a sectoral approach. The impact of the results of this study can be the basis for formulating tax policies related to cryptocurrency transactions by utilizing blockchain technology.